Implementing Metaverse in Service Activities to Prevent Corruption and the Next Steps - Al Khadafi, M. Fadhil Alif; Yasintha, Putu Nomy (Social and Political Science Faculty - Universitas Tidar, 2023)
Corruption is one of the problems that is being faced by a country because with corruption, the country can experience substantial losses. The government has worked hard to prevent and reduce the number of corruption in Indonesia, where one way is to apply or use the metaverse in service activities in Indonesia. Metaverse itself is an internet world which can be inhabited by many people by using or creating three-dimensional characters as self-images. Metaverse itself has been widely applied in various fields in various countries, including in Indonesia. Metaverse in Indonesia itself has been widely applied in several existing fields. The government itself is trying to use or apply the metaverse in service activities and so on in an effort to prevent and reduce the number of corruption in Indonesia so that later Indonesia's services can be better and also more advanced. But of course there are some parties who disagree or do not agree on this matter. The research method used in this paper is a descriptive method and collects data sourced from journals and websites related to the topic or discussion raised. The results of this paper are that this metaverse can be applied or realized in services as a prevention effort and also a tool to reduce corruption rates in services in Indonesia, but several things are needed as supports so that this can be realized well in the future.